Customer Trust sebagai Penentu Utama Loyalitas pada Bank Garansi di PT Bank Mandiri (Persero) Tbk. - Nugraheni, Searlina; Rimadias, Santi (Jurnal Keuangan dan Perbankan, 2023)
This study aims to examine and analyze the role of Relationship Marketing, Customer Satisfaction, and Customer Trust in Customer Loyalty for Bank Guarantee customers at PT Bank Mandiri (Persero) Tbk. Respondents used in this study amounted to 57 respondents who are customers of Account Officers at PT Bank Mandiri (Persero) Tbk. Data collection was carried out using an online questionnaire using Google Forms. Structural Equation Modeling is used in the analysis and uses SmartPLS 3.0 in the data processing. The results of the study explain that Customer Trust is the most dominant variable affecting Customer Loyalty for Bank Guarantee customers at PT Bank Mandiri (Persero) Tbk. Apart from Customer Trust, Customer Satisfaction is also proven to influence Customer Loyalty. Furthermore, Relationship Marketing is proven to affect Customer Trust and Customer Satisfaction. However, the test results found that Relationship Marketing did not affect Customer Loyalty. The results of the research can be used as a basis for making policies related to loyalty to bank guarantees.